Modelling of wall panels and vertical joints between them for pushover analysis of a precast wall type building - Biswal, Aparup; Reddy, K.V. Snehalatha; Sengupta, Amlan Kumar; Prasad, A. Meher (Journal of Structural Engineering, 2024)
In a precast concrete wall type building, the joints between the precast wall panels are critical interfaces of force transfer. This paper investigates the influence of modelling the grouted vertical joints (considered to be emulative joints) between the wall panels on the behaviour of a building under lateral loads. To quantify the influence, three different types of models were investigated (i) monolithic model without considering the joints, (ii) walls with gaps for the joints and (iii) walls with shear link: elements for the joints. Next, two different modelling approaches were considered: (i) reference models using two-dimensional (2D) membrane elements and (ii) simplified models using onedimensional (1D) equivalent column elements. Nonlinear static pushover analysis was carried out on standalone wall panel assemblages (with and without openings) and on a typical midrise building. To capture the material nonlinearity under increasing roof displacement (drift), multi-layered membrane elements and point plasticity in the column elements were used for the two types of models, respectively. From the observed results, it was found that a model with gaps for the joints gives an overestimation of drift and conservative estimation of lateral strength compared to the model with link elements. Also, it was observed that the behaviour of a wall panel assemblage modelled using column elements was comparable to that of a model using membrane elements till the peak strength, with acceptable variation in the post-peak behaviour. Hence, it can be inferred that a model using column elements for the panels and link elements for the joints as demonstrated in this paper, is suitable for the pushover analysis of large buildings made of precast wall panels.